Temperature-responsive peristome-structured smart surface for the unidirectional controllable motion of large droplets - Yunyun Song; Jialei Yang; Xu Zhang; Zhongqiang Zhang; Xinghao Hu; Guanggui Cheng; Yan Liu; Guojun Lv; Jianning Ding (Microsystems & Nanoengineering, 2023)
Abstract The manipulation of fast, unidirectional motion for large droplets shows important applications in the fields of fog collection and biochemical reactions. However, driving large droplets (>5 μL) to move directionally and quickly remains challenging due to the nonnegligible volume force. Herein, we fabricated a scalable, bionic peristome substrate with a microcavity width of 180 μm using a 3D printing method, which could unidirectionally drive a large water droplet (~8 μL) at a speed reaching 12.5 mm/s by temperature-responsive wettability. The substrate surface was grafted with PNIPAAm, which could reversibly change its wettability in response to temperature, thereby enabling a temperature-responsive smart surface that could regulate droplet movement in real-time by changing the temperature. A series of temperature-responsive smart patterns were designed to induce water transport along specific paths to further realize controllable droplet motion with the antibacterial treatment of predesignated areas. The ability to achieve temperature-responsive unidirectional motion and dynamic control of droplet movement could allow programmable fluidic biosensors and precision medical devices. A temperature-responsive smart surface was produced to control the unidirectional motion of large droplets between spreading and pinning movement by changing the surface wettability.